The Position of Kejawen in the Indonesian Constitution - Kristina, Ayu (Universitas Islam Negeri Raden Mas Said Surakarta, 2021)
The paradigms of world religions often influence Indonesia's general understanding of religion. Indigenous religious practices are often labeled as animistic practices. The adherents of the Indigenous religion are often regarded as worshipers of trees, mountains, and the like. Such is the case with adherents of the Indigenous religion in Java Island (Kejawen). From the results of a literature study that utilizes various literature and paradigms related to the existence of religion in Indonesia, this study tries to look further into the position of Kejawen in the Indonesian constitution. The results of this study found that Kejawen adherents still experience many discriminatory actions due to the lack of comprehensive understanding of the Indonesian people regarding the importance of symbolic recognition and the resources of Kejawen teachings. In addition, Kejawen adherents also feel they have a historical burden because they are not considered adherents of a religion